新型膜盘式柔性联轴节抗疲劳设计 - 宁向荣; 蔡显新; 陈伟 (Jixie chuandong)
Fatigue design method for the diaphragm flexible coupling is investigated,and the load spectrum,FEM stress analysis,fatigue life assessment,structural optimization methods for the flexible coupling are discussed.One of the diaphragm flexible couplings of a transmission system is design by using the proposed procedure,the computation and experiments results indicate that the procedure proposed here is efficient.